PrEP perception and experiences of adolescent and young gay and bisexual men: an intersectional analysis - Lorruan Alves dos Santos; Ramiro Fernandez Unsain; Sandra Assis Brasil; Luís Augusto Vasconcelos da Silva; Filipe Mateus Duarte; Marcia Thereza Couto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Studies indicate gaps in knowledge about the barriers to access and adhere to HIV pre-exposure prophylaxis (PrEP) in adolescents. In this article, we explore the perceptions and experiences of young gay, bisexual, and other men who have sex with men (YGBMSM) of the search, use and adherence to PrEP, considering their positions according to social markers of difference such as race/skin color, gender, sexuality, and social status. Intersectionality provides theoretical and methodological tools to interpret how the interlinking of these social markers of difference constitutes barriers and facilitators in the PrEP care continuum. The analyzed material is part of the PrEP1519 study and is comprised of 35 semi-structured interviews with YGBMSM from two Brazilian capitals (Salvador and São Paulo). The analyses suggest connections between social markers of difference, sexual cultures, and the social meanings of PrEP. Subjective, relational and symbolic aspects permeate the awareness of PrEP in the range of prevention tools. Willingness to use and adhere to PrEP is part of a learning process, production of meaning, and negotiation in the face of getting HIV and other sexually transmittable infections and the possibilities of pleasure. Thus, accessing and using PrEP makes several adolescents more informed about their vulnerabilities, leading to more informed decision-making. Interlinking the PrEP continuum of care among YGBMSM with the intersections of the social markers of difference may provide a conceptual framework to problematize the conditions and effects of implementing this prevention strategy, which could bring advantages to HIV prevention programs.